The Pattern of Thalassemia in Children at the Department of Child Health, School of Medicine University of North Sumatera/ Dr. Pirngadi Hospital, Medan - Sugiani Sinulingga; Ismet Fadil Loebis; Adi Sutjipto (Indonesian Pediatric Society, 1991)
A study of the characteristics of childhood thalassemia was conducted at the Sub Department of Pediatric Hematology, Dr. Pirngadi Hospital from June 1979 to May 1989. There were 131 cases, consisting of75 (57.25%) boys and 56 (42.75%) girls with an average of 12 admission every year. The predominant age group was 0-2 years, and the youngest was 3 months old; Javanese ethnic group appeared predominant in 36 (63.15%) cases. Clinical symptoms of anemia were found in 112 (85.49%, hepatomegaly in 91 (69.46%, hepatosplenomegaly in 84 (64.12%, without enlargement of organ in 17 (12.97%), and icterus in 6 (4.58%). Hb-Electrophoresis was done in 42 cases, revealing 26 (61.90%) with thalassemia major, 15 (35.71%) Hb E thalassemia, and 1 (2.20%) Hb H thalassemia. Hb value at the first admission in 65 (49.62%) was less than 5 g/dl, in 63 (48.09o/o) it was 5-10 g/dl and in 3 (2.29%) more than 10 g/dl.